Interacciones cuadripolares en SrZrO3 - López García, Alberto Raúl (2004)
The SrMO3 compounds with M = Ru, Zr ó Hf display similar structures. They are orthorhombic at room temperature (RT) and transform into tetragonal (14/mcm) and cubic (Pm3m) at higher temperatures. These structures are characterized by rotations of the quasi-rigid oxygen octahedron through different axes. As temperature increases the rotation axes changes at the transition temperature but the M-O distances remain almost constant (1%) in the whole temperature range. The crystallographic study of the tetragonal to cubic transformation shows that it occurs by the rotation ø(T C)→0 of the rigid oxygen octahedron about the c axis. This transition is of second order and can be described by ø(T) ∼ ø0 (TC-T)β. β is the critical exponent and was fitted to 1/2, 1/4 and 1/8 for M = Hf, Zr and Ru, respectively. The electronic structure of these compounds should follows such changes and can be studied through the measurement of the quadrupole interaction as a function of temperature. In this contribution these results obtained by Perturbed Angular Correlations spectroscopy (PAC) for SrZrO3 are discussed.